Sarcopenia is associated with autologous transplant-related outcomes in patients with lymphoma. Issue 10 (3rd October 2015) - Caram, Megan V.; Bellile, Emily L.; Englesbe, Michael J.; Terjimanian, Michael; Wang, Stewart C.; Griggs, Jennifer J.; Couriel, Daniel
Abstract : Sarcopenia is associated with treatment-related complications and shorter overall survival in patients with cancer. Psoas area indices were calculated for 121 patients with lymphoma who underwent autologous transplant. Controlling for age, body mass index, comorbidities and performance status for the 73 men included, the hazard ratio (95% confidence interval, CI) for non-relapse mortality was 2.37 (1.01, 5.58), p = 0.048 for every 100 unit decrease in total psoas index and 2.67 (1.04, 6.86), p = 0.041 for every 100 unit decrease in lean psoas index. Men with a lower total psoas index experienced more complications ( p = 0.001) and spent more days in hospital ( p = 0.03) during the transplant admission. A strong association existed between sarcopenia and number of hospital days in the 100 days following transplant among both men ( p < 0.0001) and women ( p < 0.0001). Sarcopenia may impact negative outcomes after autologous transplant thereby serving as a potentially modifiable predictor of outcomes and aiding in treatment selection.